1972
DOI: 10.1021/ja00766a029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of a Diels-Alder reaction. Butadiene and its dimers

Abstract: Synthesis and kinetic study of (I?)-( +)-1 ,l-dideuterio-2-(cyclohex-3-enyl)ethene (labeled 4vinylcyclohexene) has revealed new reactions of racemization and deuterium exchange, the former of which fixes the heat of formation of cis,trans-(and/or cis,cis) octa-3,6-diene-l,7-diyl diradical more firmly than heretofore. Redetermination of the kinetic parameters for the thermal reactions of cycloocta-l,5-diene establishes the heat of formation of the cleavage of the trans,trans (or, less probably, the cis,cis) dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 4 publications
6
45
0
Order By: Relevance
“…The asynchronous two-stage mechanism is a combination of the two earlier mechanisms. Years of controversy over which mechanism is most dominant has not reached an end, although it is likely to be an asynchronous two-stage mechanism [11].…”
Section: Dimerization Of Butadienementioning
confidence: 99%
See 1 more Smart Citation
“…The asynchronous two-stage mechanism is a combination of the two earlier mechanisms. Years of controversy over which mechanism is most dominant has not reached an end, although it is likely to be an asynchronous two-stage mechanism [11].…”
Section: Dimerization Of Butadienementioning
confidence: 99%
“…1) is suggested based on previous work [11][12][13] to predict a reaction mechanism and calculate themokinetic parameters.…”
Section: Dimerization Of Butadienementioning
confidence: 99%
“…Simple alkenes like ethylene are poor dienophiles resulting in sluggish reactions. Substituted olefins, XÀ À ÀC ¼ ¼ CÀ À ÀX 0 , are more reactive when X and/or X 0 are C ¼ ¼ C, Ar, COOR, COOH, COH, COR, COCl, CN, halogens, and many other electron-withdrawing substituents (112)(113)(114)(115)(116). A compilation of the reaction parameters between butadiene and C2ÀC4 olefins in the temperature range of 510-7508C has been published (117).…”
Section: Diels-aldermentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Previous isotope studies indicate a preference for the concerted mechanism, as supported by the Woodward and Hoffmann rules for pericyclic reactions, [8] however, the formation of a small quantity of a second product in which the isotope labels are scrambled suggests another mechanism involving biradical intermediates. [2,9,10] The biradical transition states consist of the stepwise and asynchronous biradical pathways where the stepwise involves the formation of one bond followed by the diene or dienophile rearranging itself such that the second bond can form. The asynchronous pathway is reminiscent of the concerted pathway, however, one bond forms leading to a reactive intermediate from where the second bond forms via a second, low-energy transition state.…”
Section: Introductionmentioning
confidence: 99%
“…The asynchronous pathway is reminiscent of the concerted pathway, however, one bond forms leading to a reactive intermediate from where the second bond forms via a second, low-energy transition state. [10] These mechanisms continue to be studied across different systems as new computational methods are developed and more computational power becomes available, allowing for higher correlated levels of theory to be applied to these systems. [11][12][13][14] Previous work on Diels-Alder reactions have used sophisticated complete active space (CAS) self-consistent field (SCF) calculations to account for static correlation in models of the transition states of the butadiene-ethene and butadienebutadiene cycloadditions, however, it has been shown that dynamic correlation is necessary to obtain reaction barriers that are consistent with experimental results.…”
Section: Introductionmentioning
confidence: 99%